The Influence Of Wearing Lumbo Sacral Orthosis Against The Strength Of Trunk Muscles In Case Of Low Back Pain (LBP) E.C Spondylolisthesis - Sholeh Setiyawan setiyawan (Rumah Sakit Akademik Universitas Gadjah Mada, 2021)
Background: About 80-90% of patients LBP stated that they did not do any attempts to treat his illness. Spondylolisthesis (spon-dee-lo-lis-thee-sis) is a condition where one of the spinal vertebrae to shift forward or backward with the next vertebra. The disruption that can be caused due to this condition include a painful tap on regio lumbar muscle spasm, occurs a decrease in muscle strength, limitation of motion, can also happen pain in the limbs. The purpose of this research is to know the influence of the use of the Lumbo Sacral Orthosis semirigid type to the strength of Trunk muscles in case of Low Back Pain (LBP) e. c Spondylolisthesis.Subjects and method: this type of research was quasi-experimental design pre-test and post-test design. Location of the study Area General Hospital in Yogyakarta, Gadjah Mada University Academic Hospital, Dr. Soeradji Tirtonegoro Hospital, Tugurejo Semarang Hospital. The samples in this research are 35 patients with purposive sampling.Results : there was the influence of the use of the Semirigid Type LSO against muscle flexion trunk before and after treatment (Z =-5.099 with p value = 0.000), trunk rotation muscle (Z =-4.600 with p value = 0.000), trunk extension muscle strength (Z =-4.472 with p value = 0.000).Conclusion: As for the results of this research are the greatest influence has decreased muscle strength of the trunk after wearing the LSO within one month is on the muscle group Flexor (0.75), then extensor muscles (0.58) and rotator trunk muscles (0.65).Keywords: Lumbo Sacral Orthosis semirigid type, The strength of Trunk muscles, Low Back Pain (LBP) e. c Spondylolisthesis.